Evaluation of natural additives for modification concrete - Nur Aqma Nadira , Mazuki (2012)
Bentonite is a rock composed essentially of a crystalline clay-like mineral formed by devitrification and the accompanying chemical alteration of a glassy igneous material, usually a tuff or volcanic ash; and it often contains variable proportions of accessory crystal grains that were originally phenocrysts in the volcanic glass. This project report presents an investigation carried out on study the compressive strength. of concrete with the possibility of using bentonite as natural additives in the concrete mix. By following DoE mix design, the mix material proportion, Ordinary Portland cement (OPC) was made to have target strength of 40N/mm 2 . In the same condition, this research also consists of OPC concrete with 0.25% and 0.50 % unheated and heated bentonite was prepared by weight of the mix proportions. The bentonite used in this research is the readymade materials and ii will be crushed with Jaw Crusher and then it will be heated in Furnace with the different temperatures which are 200°C-800°C with the increment of 200°C within 1 hour respectively. A total of 55 samples concrete cubes of sizes 150 x 150 x 150 mm with different percentages by weights were cast, and tested within the age of 7, 14 and 28 days curing period. A compressive strength result reveals that the compressive strength containing bentonite is higher than the normal OPC concrete. It can be concluded that it is possible to used bentonite which is a part of clay mineral as natural additives in the concrete to increase the compressive strength of the concrete.